Skills improvement needs of electronics work trade teachers in science and technical colleges in North East, Nigeria - Musa Dauda, Hassan Bello; Deba, Ahmad A. (Kashere Journal of Education, 2023)
The study determined the Skills improvement needs of electronics works trade teachers in science and technical colleges in North East, Nigeria. The study adopted descriptive survey research design. Two research questions was raised and answered and two corresponding hypotheses was tested at 0.05 level of significance. The population of the study consisted of 220 teachers of electronics works trade from 34 science and technical colleges, and 140 teachers was used as sample for the study. The instrument used for collection data was a 16 items structured questionnaire. The instrument was developed by the researchers after extensive literature review based on the specific objectives of the study. The instrument was validated by three research experts while the reliability index of 0.89 was obtained using Cronbach’s alpha. The findings of the study revealed that radio and electronic system repairs and maintenance, television repairs and maintenance skills improvement needs of electronics works trade teachers. The recommendations include among others that government and other training institution should improve skills of electronics work trade teachers in public science and technical colleges in television repairs and maintenance.